HIV-mediated immune aging in young adults infected perinatally or during childhood. (1st September 2019) - Fastenackels, Solène; Sauce, Delphine; Vigouroux, Corinne; Avettand-Fènoël, Véronique; Bastard, Jean-Philippe; Fellahi, Soraya; Nailler, Laura; Arezes, Elisa; Rouzioux, Christine; Warszawski, Josiane; Viard, Jean Paul; Appay, Victor
Abstract : Background: HIV-infected patients progressing towards disease present a premature immune aging profile, characterized by the exhaustion of lymphopoiesis. The development of these anomalies may be prevented in young HIV-infected patients owing to their robust immune resources and lymphocyte regeneration capacities. Methods: An immunomonitoring substudy was designed for young adults aged between 18 and 25 years, living with HIV since childhood included in the national ANRS Co19 COVERTE Cohort. We compared markers associated with immune aging, including the frequency of circulating hematopoietic progenitors and the phenotype of lymphocyte populations, with those of patients infected with HIV in adulthood. Results: HIV-infected young adults displayed decreasing numbers of CD34 + hematopoietic progenitors and mature lymphocytes, indicative of general lymphopenia and reminiscent of the alterations found in patients infected in adulthood or uninfected elderly people. This highlights the strong impact of HIV on the immune system despite patient's young age at infection. Immune aging-related alterations were particularly obvious in young patients who presented high viral loads. Conclusion: HIV-infected young adults can present increased markers of immune activation and senescence, related to uncontrolled viral replication. This highlights the issue of noncompliance to antiretroviral therapy in patients at a young age, resulting in loss of viral control, premature immunosenescence, and potentially irreversible damage of their lymphopoietic system. Abstract : Supplemental Digital Content is available in the text